On the Optimal Coefficient of Efficiency of a Semi-Markov System in the Scheme of Phase Lumping - Vovkodav, N. G.; Shlepakov, L. N. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
By using methods of the theory of semi-Markov processes, we analyze the problem of detecting signals in a multichannel system. We construct an optimal strategy for the motion of a search device in a multichannel system and obtain the corresponding estimate for the search efficiency.